1994
DOI: 10.1111/j.1469-8137.1994.tb02987.x
|View full text |Cite
|
Sign up to set email alerts
|

Acclimation of photosystem II in a cyanobacterium and a eukaryotic green alga to high and fluctuating photosynthetic photon flux densities, simulating light regimes induced by mixing in lakes

Abstract: SUMMARYPhotoacclimation of Scenedesmus protuberans F'ritsch and Microcystis aeruginosa Kutzing emend. Elenkin to high and fluctuating PPFD was studied in continuous cultures with computer-controlled variable light regimes. The aim of the work was to provide a better understanding of species-specific acclimation to high PPFD (as encountered by cyanobacteria in surface waterblooms), and of suppression of the growth of colony-forming cyanobacteria during periods of prolonged mixing in lakes. The dynamics of a set… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
85
1

Year Published

1996
1996
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 109 publications
(96 citation statements)
references
References 103 publications
(132 reference statements)
10
85
1
Order By: Relevance
“…Eukaryotic algae such as green algae and diatoms seem better adapted to these fluctuations (Flameling and Kromkamp 1997;Nicklisch 1998;Litchman 2000), while many cyanobacteria seem more sensitive. A study by Ibelings et al (1994) in laboratory cultures showed that the cyanobacterium Microcystis was more sensitive to changes in photon irradiance than the green alga Scenedesmus. In a field experiment, Mitrovic et al (2003) showed a decrease in Microcystis (but also of Scenedesmus) under fluctuating light, while the diatom Skeletonema was found to increase compared to static light conditions.…”
Section: The Working Mechanismmentioning
confidence: 99%
“…Eukaryotic algae such as green algae and diatoms seem better adapted to these fluctuations (Flameling and Kromkamp 1997;Nicklisch 1998;Litchman 2000), while many cyanobacteria seem more sensitive. A study by Ibelings et al (1994) in laboratory cultures showed that the cyanobacterium Microcystis was more sensitive to changes in photon irradiance than the green alga Scenedesmus. In a field experiment, Mitrovic et al (2003) showed a decrease in Microcystis (but also of Scenedesmus) under fluctuating light, while the diatom Skeletonema was found to increase compared to static light conditions.…”
Section: The Working Mechanismmentioning
confidence: 99%
“…In contrast to homogeneously distributed PPFRs in the dilute monoculture experiments, the cells in the dense competition experiment experienced a continuously changing PPFR upon circulation in the vessel. Generally speaking, there is no doubt that a fluctuating PPFR affects the growth of phototrophs (see, for example, Ibelings et al (1994) ; Schubert et al (1995)). If Aphanizomenon is less able to withstand such a dynamic light regime than Anabaena, this could explain the outcome of the competition experiment.…”
Section: Light-limited Growth Of Diazotrophsmentioning
confidence: 99%
“…Chlorophyll a fluorescence measurements were made in situ at room temperature using the saturation-pulse method described by Schreiber, Schliwa & Bilger (1986), and the experimental setup described by Ibelings, Kroon & Mur (1994). A saturating pulse of light (12 000 µmol photons m −# s −" , 0n8 s), which induced maximal fluorescence (all PSII reaction centres closed), was administered at 15-min intervals.…”
Section: Chlorophyll Fluorescencementioning
confidence: 99%
“…Reduction of growth of Microcystis in an artificially mixed lake has been described by Toetz (1981) . Not only will it no longer benefit from its buoyancy controlled vertical positioning, but Microcystis also showed a poor acclimation to light regimes simulating those induced by mixing in lakes (Ibelings et al ., 1994) .…”
Section: Introductionmentioning
confidence: 99%